Are unresponsive dilated pupils an indicator for brain death? an evaluation of Edinger Westphal nucleus in rabbits with brain death (Annals of Medical Research, 2021)
Aim: To investigate a relationship between unresponsive pupils and severity of neurodegeneration in Edinger Westphal nucleus (EWN) of animals diagnosed with brain death.Material and Methods: A total of 24 New Zealand white rabbits were used. The animals were divided into three groups, as control group (n=5), sham (n=5) and subarachnoid hemorrhage (SAH) group (n=14). Pupil diameters were measured after giving 2 mL of physiological saline for sham and 2 ml non‑heparinized autologous arterial blood for the study group into the cisterna magna. Brain death was diagnosed in 10 rabbits in the SAH group. Then all animals were sacrificed. The brains, oculomotor nerves of all animals were extracted and stored in 10% formalin solutions for histopathological examination.Results:TThe mean neuron numbers of Edinger Westphal nucleus was 253±43/mm3 in the control group; 244±12/mm3 in the sham group and 236±12/mm3 in dead unresponsive animals. Pupil diameters and degenerated neuron density of EWN in control, sham and SAH groups were found as follows, respectively: 8960±990µm-3±1/mm3; 10543±1.123µm-13±4/mm3 and 13540±1.356µm-63±11/mm3 (P0.005). There was a positive relationship between degenerated neuron density of the EWN and pupil diameters (P0.001). The mean nondegenerated neuron numbers were 170±32/mm3 in unresponsive pupils of examined animals.Conclusion: In the absence of electrocardiographic/electroencephalographic functions, unresponsive pupils could not indicate real brain death.
Keywords: Brain death; unresponsive pupils; Edinger Westphal nucleus; degenerated neuron.